Adherence to imatinib among patients attending Saskatchewan Cancer Agency Pharmacies. (December 2015) - Dicus, Melissa; Lyons, Barry; Olson, Colleen; Tran, David A; Blackburn, David F
Rationale: Chronic use of imatinib confers an important survival benefit for individuals with chronic myeloid leukemia. In Saskatchewan, the provincial cancer agency addresses important barriers to adherence by providing imatinib at no cost through specialized cancer centers. Objective: To describe adherence to imatinib dispensed through the Saskatchewan Cancer Agency. Study design and methods: We conducted a retrospective analysis of electronic pharmacy dispensation records from the Saskatchewan Cancer Agency. All dispensations for imatinib classified for hematologic malignancies were electronically abstracted by cancer center personnel and securely forwarded to investigators with all meaningful patient identifiers removed. All subjects receiving a new dispensation (i.e. using a 6-month washout period) for imatinib between 1 June 2004 and 31 December 2011 were included. The primary endpoint was optimal adherence to imatinib during the first year of therapy, defined as a medication possession ratio ≥ 80%. Results: Ninety-one subjects were started on imatinib during the observation period. During the first year of therapy, 82.4% (75/91) maintained a medication possession ratio ≥ 80%. The percentage of individuals maintaining optimal adherence decreased only slightly when the observation period was extended to 2 (78.4%) or 3 years (78.8%). Conclusions: Non-adherence to imatinib is relatively infrequent when provided by the Saskatchewan Cancer Agency.